Relationship between Human Aging Muscle and Oxidative System Pathway. (17th May 2012) - Doria, Enrico; Buonocore, Daniela; Focarelli, Angela; Marzatico, Fulvio
Abstract : Ageing is a complex process that in muscle is usually associated with a decrease in mass, strength, and velocity of contraction. One of the most striking effects of ageing on muscle is known as sarcopenia. This inevitable biological process is characterized by a general decline in the physiological and biochemical functions of the major systems. At the cellular level, aging is caused by a progressive decline in mitochondrial function that results in the accumulation of reactive oxygen species (ROS) generated by the addition of a single electron to the oxygen molecule. The aging process is characterized by an imbalance between an increase in the production of reactive oxygen species in the organism and the antioxidant defences as a whole. The goal of this review is to examine the results of existing studies on oxidative stress in aging human skeletal muscles, taking into account different physiological factors (sex, fibre composition, muscle type, and function).